Leaf rust and stripe rust resistance genes Lr54 and Yr37 transferred to wheat from Aegilops kotschyi - Marais, G. F.; McCallum, B.; Snyman, J. E.; Pretorius, Z. A.; Marais, A. S. (Plant breeding, 2005)
The tendency of unpaired meiotic chromosomes to undergo centric misdivision was exploited to translocate leaf rust and stripe rust resistance genes from an Aegilops kotschyi addition chromosome to a group 2 chromosome of wheat. Monosomic and telosomic analyses showed that the translocation occurred to wheat chromosome arm 2DL. The introgressed region did not pair with the corresponding wheat 2DL telosome during meiosis suggesting that a whole arm may have been transferred. Female transmission of the resistance was about 55% whereas male transmission was strongly preferential (96%). The symbols Lr54 and Yr37 are proposed to designate the new resistance genes.